THE FORMATION OF THE TRANSPORT SYSTEM AND ITS IMPACT ON THE TRANSFORMATION OF THE FUEL AND ENERGY COMPLEX OF UKRAINE - Pokotilov, A. A.; Sytnyk, V. V. (Science and Transport Progress, 2006)
Ways of formation of the transport system have been provided its influence on the transformation of fuel & power generation complex of Ukraine in the conditions of establishment of modern market economy.